Answer:
3hr 30min
Step-by-step explanation:
3hr 30min
This looks like an incomplete answer to me...
I cannot see any diagram or window or opening, or any lines that indicate they are line AC or BD.
Answer:
Where is the table?
Step-by-step explanation:
The translation of the given sentence into an equation is: 7(b + 3) = 1.
<h3>How to Translate a Sentence into an Equation?</h3>
Variables can be used to represent an unknown quantity when translating statements into equation. The word "times" is represented as or means "×" (multiplication). "Sum" means addition as well.
Thus, the sentence given can be translated as shown below:
The unknown number is represented as variable b.
"The sum of a number (b) and 3" would be translated as: b + 3.
"Seven (7) times the sum of a number and 3 (b + 3)" would therefore be: 7(b + 3).
Therefore, translating the whole sentence into an equation, we would have:
7(b + 3) = 1.
Thus, the translation of the given sentence into an equation is: 7(b + 3) = 1.
Learn more about equation on:
brainly.com/question/13155862
#SPJ1
A ) equation would be X = Z / Y
B ) if X = 9 ------------> Y = 1/7
X = 21 ----------> Y = ?
21*1/7 = 21/7 , 21/7÷9 = 21*9/7 = 27
so Y equal 27